Assessing participation : a debate from South Asia - Bastian, Sunil; Bastian, Sunil; Bastian, Nicola; Duryog Nivaran (Network : Colombo, Sri Lanka) (Delhi, India : Konark Publishers, 1996)
Contributed papers presented at the workshop organized by Duryog Nivaran in Nov. 1995 held in Colombo; deals on participatory development.
Includes bibliographical references (p. [273]-283) and index.
Keywords: Rural development -- Sri Lanka -- Congresses; Sri Lanka -- Social conditions -- Congresses; Sri Lanka -- Politics and government -- Congresses